Evaluation and driving force analysis of relative effectiveness in the giant panda national park in Sichuan, China - Bao Meng; Bao Meng; Mengchao Wang; Zhifeng Zhang; Hongyi Pan (Frontiers in Environmental Science)
Empirical analysis of the relative effectiveness of the Giant Panda National Park (GPNP) system can promote the optimization and improvement of its management level. Normalized Difference Vegetation Index (NDVI) is a key indicator to measure the health of ecosystems, which can effectively quantitatively reveal the spatial and temporal changes of ecological protection effects. This study evaluated the relative effectiveness of Normalized Difference Vegetation Index (NDVI) protection in the Sichuan area of the GPNP from 2000 to 2020 using the propensity score matching model (PSM). It also explored the influencing factors and interactions of each period by combining the Optimal Parameter-based Geographical Detector Model (OPGD). The results showed that: 1) The study area’s Relative Effectiveness Index (REI) was positive, suggesting effective ecological protection. The REI fell from 0.044 in 2000 to 0.031 in 2015 and although it then increased to 0.034 in 2020 to a small extent, the REI showed an overall decreasing trend, and the conservation effect has weakened. 2)The REI change patterns varied in different functional zones of the area, with a general fluctuation and decline, in which the Minshan and Baishuijiang Core Protection Area (MBJ-CPA) as a whole first rise and then fall, and it is the area with the best relative effectiveness of protection. 3) Natural factors such as temperature and elevation are the main factors affecting NDVI, while the influence of policy and economic factors such as the level of protected areas and distance to towns are increasing. The Qionglaishan and Adjacent Areas General Control Area (QLA-GCA) is dominated by the interaction of landscape pattern index with its remaining factors, and the rest of the functional areas are dominated by the interaction of natural factors such as temperature, evapotranspiration with its remaining factors. Therefore, in future development, the Qionglaishan Areas need to pay more attention to the optimization of landscape patterns, while the other areas need to pay more attention to the impact of climate change on the ecosystem. This study can provide a reference for the improvement and management of ecological protection of the GPNP system in the future.